Negative Color Aftereffect in the Absence of a Colored Stimulus. (February 2022) - Sivkovich Fagin, Oksana; Mack, Arien
Negative color aftereffects normally occur following prolonged observation of colored surfaces and are generally attributed to sensory adaptation of opponent processes responsible for color vision. We describe evidence that negative color aftereffects, no different from those that occur when actually viewing red, are perceived in the complete absence of a colored stimulus by highly suggestible persons who are hypnotized and hallucinate seeing red. Highly suggestible participants also excel at imagining color although this is less likely to generate an aftereffect suggesting that there is more to hallucinating than imagining. Our results are clear evidence that sensory adaptation is not necessary for negative color aftereffects.